Healthy dietary patterns linked to Brazilian adolescents' school meal adherence - Mendalli Froelich; Amanda Cristina de Souza Andrade; Paulo Rogério Melo Rodrigues; Sanna Sinikka Talvia; Christina Holub; Diana Barbosa Cunha; Larissa Loures Mendes; Ana Paula Muraro (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: This study aimed to verify the association between adherence to school meals provided by the National School Feeding Program and dietary patterns in adolescents from Brazilian public schools. Methods: Data from the 2019 National School Health Survey were used, with a nationally representative sample of Brazilian school adolescents (n=53,477; 13-17 years old). Food consumption of healthy and unhealthy food markers was obtained from a food consumption questionnaire. Regular consumption was considered ≥5 times/week. Latent class analysis was used to identify dietary patterns whose association with adherence to school meals was evaluated by multinomial logistic regression models, with adjustment for sociodemographic and eating behavior variables. Results: Three dietary patterns were identified: "unhealthy" - higher consumption of soft drinks and sweets (9.2% of adolescents); "healthy" - higher consumption of beans, vegetables, and fruits (27.1%); and "monotonous" - higher consumption of beans (63.7%). High adherence to school meals (every day) and unsatisfactory adherence (1-4 times/week) were positively associated with the healthy pattern even after adjustment for possible potential confounders (OR 1.37, 95%CI 1.23-1.52; OR 1.20, 95%CI 1.10-1.30, respectively). Conclusion: The results showed that the consumption of school meals offered by the National School Feeding Program can contribute to healthy eating habits among Brazilian adolescents.